Uma revisão da gravitação bidimensional do ponto de vista da gravitação quântica de Loops - Costa, Alex Rios (2007)
We make an introductory study of the formalism of Loop Quantum Gravity. A brief review of the cononical formulation of General Relativity is performed, in order to motivate the introduction of the loop formalism. We show how it can be adapted to bidimensional gravity, more specifically to the Jackiw-Teitelboim model, for which we make a complete analisys of the canonical formulation using the first order formalism. We finally comment on how the quantization procedure could be implemented in this model